2008
DOI: 10.1021/ie070324x
|View full text |Cite
|
Sign up to set email alerts
|

Scrubbing of CO2 Greenhouse Gases, Accompanied by Precipitation in a Continuous Bubble-Column Scrubber

Abstract: A continuous bubble-column scrubber that absorbs carbon dioxide (CO2) gas using an alkaline solution under a pH-stat condition was used to explore the effects of the pH of the solution, gas concentration, gas-superficial velocity, and liquid-flow rate on the absorption rate and volumetric mass-transfer coefficient of CO2. When the scrubbing factor was evaluated, this scrubber outperformed other scrubbers. Correlations of local volumetric mass-transfer coefficients with process variables are presented here and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 19 publications
5
34
0
Order By: Relevance
“…The dissolution of gaseous CO 2 in solution is generally the first rate-limiting step in direct carbonation reactions [27], but it can be enhanced by increasing the CO 2 flow rate [28] when working at atmospheric pressure and thereby ensuring that excess carbonate ions are present relative to calcium ions. However, a further increase of the flow rate to more than 29.33 ℓ CO 2 /min/kg CaS r had little effect on the overall reaction time (Table 5 and Figure 6).…”
Section: Figurementioning
confidence: 99%
“…The dissolution of gaseous CO 2 in solution is generally the first rate-limiting step in direct carbonation reactions [27], but it can be enhanced by increasing the CO 2 flow rate [28] when working at atmospheric pressure and thereby ensuring that excess carbonate ions are present relative to calcium ions. However, a further increase of the flow rate to more than 29.33 ℓ CO 2 /min/kg CaS r had little effect on the overall reaction time (Table 5 and Figure 6).…”
Section: Figurementioning
confidence: 99%
“…In order to further determine the mass-transfer coefficient, it was assumed that two-film model was used to describe CO2 mass transfer (Chen et al, 2008). Thus, the overall mass-transfer coefficient can be expressed as follows:…”
Section: Determination Of Mass-transfer Coefficientmentioning
confidence: 99%
“…The results can provide references for bubble column design. The bubble column features simple structure, easy operation, cost efficiency and excellent scrubbing factor as compared with other scrubbers (Chen et al, 2008;Lin et al, 2003;Sauer and Hempel, 1987;Aroonwilas et al, 1999), without mechanical heat production. Thus, recovery of CO2 using bubble columns can reduce costs and save energy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these methods, the absorption of carbon dioxide in an alkaline solution with crystallization has also been adopted to explore the removal of carbon dioxide from waste gas (Chen et al, 2008). This approach, with the production of carbonate by means of reactive crystallization, has been found to be effective.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this, they found packed bed with structured packing (Aroonwilas & Tontiwachwuthiku, 1997) gives a higher overall mass-transfer coefficient as compared with other scrubbers. On the other hand, Chen et al (2008) found that the performance of scrubber could be estimated by using scrubbing factor, a definition of removal of 1 mole CO 2 gas per mole of absorbent and per liter of scrubber. In this manner, a bubble-column scrubber is the first choice.…”
Section: Introductionmentioning
confidence: 99%